PELATIHAN PENGGUNAAN TEAM VIEWER UNTUK MEREMOTE KOMPUTER JARAK JAUH PADA SISWA/I SMK TEKNIK KOMPUTER JARINGAN YAYASAN PENDIDIKAN CERDAS BANGSA - Jimmy Nganta Ginting; Sastra Wandi Nduru (JOURNAL OF COMMUNITY DEDICATION, 2023)
The application of Team Viewer application technology is one of the digital innovations to remotely control computers/laptops. The population of this training is all students of class X and XI Computer Network Engineering of SMK Swasta Cerdas Bangsa, North Sumatra Province, Deli Serdang Regency, totaling 40 students, while the sample of this study was taken from a population of 20 students. The sampling technique used is the purposive sampling technique. The practical technique used in this training is direct observation of the activity process and observations carried out directly by students during the practicum activities. The technique used by students is the number of students divided into 20 groups, 1 group of 2 people and each group must register on the teamviewer application in order to be able to log in to the application so that the process of implementing the practicum is successful. TeamViewer software is one step in helping students carry out practicum activities online. This training aims to determine students' understanding in implementing TeamViewer software. The purpose of this study was to determine how the process of implementing TeamViewer software is and to see students' responses to the results of using TeamViewer in practicum activities for the subject of Computer Network Systems. Based on the results of the training carried out, it is known that the implementation of the computer network system subject practicum can be carried out well by looking at the results of the observation of the implementation of activities at a percentage of 100% and the results of the observation of the use of the Teamviewer remote desktop application in the implementation of the implementation are also at a percentage of 100%. Thus it can be concluded that the implementation of remote practicums can be carried out by utilizing the Remote Desktop Teamviewer application.